A cross-sectional study on the long-term impact of COVID-19: Symptoms, disability and daily functioning - Soraya Maart; Rebecca A. Hofmeyr; Justin J. Muller; Lehlohonlo B. Tserere (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Evidence suggests that survivors of coronavirus disease 2019 (COVID-19) experience ongoing symptoms, which is known as long COVID, or post-COVID syndrome. Approximately 100 million people globally are experiencing long COVID symptoms. Post-COVID syndrome (PCS) has debilitating effects on functioning and quality of life, potentially qualifying it as a disability.